Towards a Synthesis of voseo tuteante: Notes about its history and variation (Ogigia. Revista Electrónica de Estudios Hispánicos, 2021)
Voseo tuteante is a most relevant isogloss of Spanish worldwide, with a double value. As a unit, voseo splits Spanish America in two, between those who use it and those who do not. It is crucial to identify and understand its defining properties that distinguish it from other types of voseo, synchronically and diachronically. As a variable structure it also helps draw lines ever finer about who use it and how. With this goal in mind, the best method is a parametric analysis that indicates which parts of it can vary and which are the options for those variables.
Keywords: Voseo; allocution; history; diachrony; Spanish.